Direct Data-Driven Control of Cavity Tuners in Particle Accelerators. Issue 15 (2018) - Zanchettin, Andrea M.; Formentin, Simone; Loddo, Riccardo; Paparella, Rocco
Abstract: X-Ray Free Electron Lasers (XFELs) are the next generation of X-rays sources delivering dramatical improvements over synchrotron radiation in terms of brilliance, pulse length and coherence. While obtaining such X-ray radiations, the high gradients of the accelerating electromagnetic field, external vibrations and pressure fluctuations may cause deformations of the cavities where the electrons are accelerated. This lowers the efficiency of the linear accelerator (linac) and degrades the beam quality. To contrast this phenomenon, known as "detuning", suitable mechanical compensators of cavity deformations are needed. In this paper, we propose a direct data-driven approach for the synthesis of such systems, as an alternative to the on-line iterative methods currently in use. The effectiveness of the proposed approach is shown on a complex linac simulator.